A preliminary study of the oral microbiota in Chinese patients with Sjögren's syndrome. (October 2016) - Li, Miaoran; Zou, Yan; Jiang, Qian; Jiang, Lindi; Yu, Qiang; Ding, Xiaojun; Yu, Youcheng
Highlights: With high through-put sequencing, we investigated the diversity of oral microbiota in Sjögren's syndrome (SS). The relative abundance of Proteobacteria in SS group was lower compared to that of healthy controls. Genera with higher relative abundance in SS group included Leucobacter, Delftia, Pseudochrobactrum, Ralstonia and Mitsuaria . Genus with lower relative abundance in SS group was Haemophilus, Neisseria, Comamona, Granulicatella and Limnohabitans . Prednisone acetas influences the diversity of buccal mucosa bacterial communities in SS patients. Abstract: Objective: To investigate the oral microbiota in Sjögren's syndrome (SS) as opposed to that of healthy subjects. Study design: Ten patients with primary SS, [6 patients daily taking stable dosage of hydroxychloroquine (HC) and 4 patients taking hydroxychloroquine combined with Prednisone acetas (HC + PA)], along with 10 age-matched healthy controls were examined in regard of number of teeth, stimulated/unstimulated saliva secretion rate. Microflora on bilateral buccal mucosa was analyzed by high throughput sequencing. Statistical analyses were performed using the chi-square test, t test and Mann-Whitney U test. The Venn diagrams and Redundancy Analysis (RDA) were also used to evaluate effects of the disease and treatment on the bacterial community composition. Results: The relative abundance of Proteobacteria in SS group was lower compared to controls ( P  = 0.002). The total richness of genera for all groups was 339. The numbers of genera in SS group and in control group were 248 and 270, respectively. Some taxa with different prevalence and/or relative abundance were found between two groups. Conclusions: SS affects the oral microbiota and SS patients carry a different and less diverse microorganism community compared with healthy subjects. Prednisone acetas is an influence on the oral microbiome. This study provides a basic data on the oral flora in SS patients.